Exploring glucagon-like peptide-1 receptor agonists as potential disease-modifying agent in psychiatric and neurodevelopmental conditions: evidence from a drug target Mendelian randomization - Lingfeng Zhang; Xiang Chen; Yantao Xu; Jiachen Liu; Zhongchun Liu (BMC Psychiatry)
Abstract Background Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have recently received Food and Drug Administration (FDA) approval for obesity management. However, the causal relationship between GLP-1RAs and psychiatric and neurodevelopmental conditions remains unclear. Methods We used Mendelian randomization (MR) to investigate the association between genetically proxied GLP-1RA exposure and 12 psychiatric and neurodevelopmental conditions. Genetic instruments were derived from cis-eQTLs for GLP-1R, and analyses were conducted using large-scale GWAS datasets. Type 2 diabetes was included as a positive control (107,133 cases, 656,672 controls). Findings were assessed across multiple independent datasets, including FinnGen, Psychiatric Genomics Consortium (PGC), and UK Biobank, and were synthesized through meta-analysis. Result Genetically proxied GLP-1RA exposure was associated with a lower risk of schizophrenia (OR = 0.72, 95% CI [0.61–0.86]), bipolar disorder (OR = 0.91, 95% CI [0.88–0.94]), bulimia nervosa (OR = 0.34, 95% CI [0.23–0.52]), post-traumatic stress disorder (PTSD) (OR = 0.45, 95% CI [0.31–0.67]), and autism (OR = 0.55, 95% CI [0.32–0.93]), all P < 0.001. Conversely, higher GLP-1R expression was associated with an increased risk of obsessive-compulsive disorder (OCD) (OR = 2.30, 95% CI [1.26–4.22], P < 0.001). No significant associations were observed for anorexia nervosa, broad depression, major depressive disorder (MDD), or suicide and intentional self-harm. Sensitivity analyses and heterogeneity assessments supported the robustness of these findings across multiple cohorts. Limitations GLP-1RAs reduced some psychiatric and neurodevelopmental conditions but lacked extensive evidence. Bulimia nervosa and PTSD evidence was limited to one database. Bipolar disorder and OCD results varied, with significant OCD findings in one database. The study’s European ancestry focus limits generalizability. Rare disorders and disease progression were not examined. Future research needs diverse populations, long-term follow-ups, and treatment exploration. Conclusions Our study suggests that GLP-1RAs may decrease the risk of schizophrenia, anxiety disorders, bipolar disorder, bulimia nervosa, PTSD, and autism, but may increase the risk of OCD. Larger randomized controlled trials with long-term follow-up are necessary to confirm these associations and evaluate the risk-benefit ratios. Clinical trial number Not applicable.